Cost-utility analysis of total knee arthroplasty for osteoarthritis in a regional medical center in China - Qi Gui; Xinghuo Zhang; Liang Liu; Feng Zhao; Wenhao Cheng; Yakui Zhang (Health Economics Review, 2019)
Background: To analyze the cost-effective ratio of total knee arthroplasty (TKA) in the osteoarthritis (OA) treatment of at a regional medical center in China. Methods: One hundred thirty-nine patients with osteoarthritis who underwent TKA at the Department of Osteoarthritis in Luhe hospital (Tongzhou, Beijing) from January 2011 to January 2012 were followed up. Their health-related quality of life (HRQoL) was evaluated using Short-Form Health Survey (SF) -36 Chinese version, and compared with those of the normal population to assess quality-adjusted life years (QALYs) gained after surgery for its effectiveness of the treatment. The total expense was the cost of patient hospitalization. The cost per QALY was calculated. The cost-benefit ratio (CBR) was expressed as a ratio of each QALY's expenditure to per capita gross domestic product (GDP). Factors affecting the cost, including age, gender, length of stay, and ICU experience, were also considered. Results: The total hospitalization fee was ?8,053,736.68, ?57,940.55 in average, of which, 81.59% constituted out-ofpocket expenses. The SF-36 scores were as follows: Physical Function: 25.14, Role Physical: 7.12, Bodily Pain: 9.60, Role emotional: 5.58, Vitality: 19.9, Mental Health: 25.84, Social Function: 9.86 and General Health: 21.15. Compared with normal people of the same age and sex, a total of ?2487.74 QALYs and ?3237.37/QALY were gained, 10% less than the regional GDP per capita. The cost-effective ratio of TKA for osteoarthritis in China was 1: 10.78. The main cost of the patient was the cost of prosthesis (61.78%). The average cost afforded by patients' themselves was ?47,242.64 after the deduction of government subsidies. There were ?31,306.64 difference compared with the annual average income of the local people. The cost might be affected by length of stay and ICU experience. Longer stay caused more cost of treatment. Patients who remained in ICU after surgery had higher overall costs and blood transfusion costs. Conclusion: The factors that affect TKA cost are hospital and postsurgical ICU stay. It is cost-effective for regional medical care center to treat osteoarthritis using TKA economically. However, considering the average income of patients in the area, it is necessary to reduce the cost of the treatment.
Keywords: 330; TKA; QALY; Cost analysis; Cost utility ratio; Regional medical center